Geographic information system software application developed by a regional emergency agency. (October 2015) - Martín-Gómez, César; Vergara-Falces, Javier; Elvira-Zalduegui, Asier
Abstract: This paper presents a methodology for risk analysis and assessment to manage territorial data based on Geographical Information Systems from the viewpoints of climatology, geography, disaster science, environmental science, fire safety and urban services. The results in this methodology are intended to support local and provincial government agencies to: make resource allocation decisions; make high-level planning decisions and raise public awareness of disasters risk, its causes, and ways to manage it. The Autonomous Community of Navarra, as a result of a special administrative status, possesses a number of specific features that have let it build up a high technological development in several fields. The main areas of research are healthcare and renewable energies, but also focused in the implementation of security systems at territorial level.These advances and particularities of the GIS software used by the fire fighters of this community will be the ones shown in this paper, as well as its prospective improvements in the collaboration with the experts responsible for urban planning of a School of Architecture.